Extracorporeal Membrane Oxygenation after Heart Transplantation: Impact of Type of Cannulation - Mehdiani, Arash; Immohr, Moritz Benjamin; Boettger, Charlotte; Dalyanoglu, Hannan; Scheiber, Daniel; Westenfeld, Ralf; Aubin, Hug; Akhyari, Payam; Saeed, Diyar; Lichtenberg, Artur; Boeken, Udo (The Thoracic and Cardiovascular Surgeon, 2020)
Background Primary graft dysfunction (PGD) is a common cause of early death after heart transplantation (htx). The use of extracorporeal life support (ECLS) after htx has increased during the last years. It is still discussed controversially whether peripheral cannulation is favorable compared to central cannulation. We aimed to compare both cannulation techniques.Methods Ninety patients underwent htx in our department between 2010 and 2017. Twenty-five patients were treated with ECLS due to PGD (10 central extracorporeal membrane oxygenator [cECMO] and 15 peripheral extracorporeal membrane oxygenator [pECMO] cannulation). Pre- and intraoperative parameters were comparable between both groups.Results Thirty-day mortality was comparable between the ECLS-groups (cECMO: 30%; pECMO: 40%, p = 0.691). Survival at 1 year (n = 18) was 40 and 30.8% for cECMO and pECMO, respectively. The incidence of postoperative renal failure, stroke, limb ischemia, and infection was comparable between both groups. We also did not find significant differences in duration of mechanical ventilation, intensive care unit stay, or in-hospital stay. The incidence of bleeding complications was also similar (cECMO: 60%; pECMO: 67%). Potential differences in support duration in pECMO group (10.4 ± 9.3 vs. 5.7 ± 4.7 days, p = 0.110) did not reach statistical significance.Conclusions In patients supported for PGD, peripheral and central cannulation strategies are safe and feasible for prolonged venoarterial ECMO support. There was no increase in bleeding after central implantation. With regard to the potential complications of a pECMO, we think that aortic cannulation with tunneling of the cannula and closure of the chest could be a good option in patients with PGD after htx.
Keywords: transplantation; heart; extracorporeal membrane oxygenation; ECMO